El Tratado de Lisboa y las modificaciones en la organización parlamentaria europea. La implantación del mecanismo de alerta temprana en el complejo sistema parlamentario español (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2010)
The entry into force of the Lisbon Treaty and the regulation of early warning mechanism in the control of the subsidiarity principle, requires to carry out legislative and organizational reforms in the national parliaments of the Member States. The aim is undoubtedly to improve the democratic legitimacy and the quality and efficiency of the legislative process at European Union level through the involvement of national parliaments. The Spanish Parliament approved the Law 22/2009 of December 22 nd adapting its internal procedures to the new guidelines by giving more responsibility to the Joint Committee on European Union Affairs. The article has also sought to reflect the complexity of the Spanish descentralization system.